Differences in rhetorical and linguistic features in medical oral case presentations of medical experts and medical students - Khan, Munir (2018)
Oral case presentation (henceforth, OCP) is a professional form of discourse between physician and physician-in-training focusing on patients’ ailment, diagnosis, and treatment. Medical experts are often dissatisfied with medical students’ poor mastery of the OCP genre. Eventually, they offer them sufficient implicit instructions to improve not only the formal structure but also the rhetorical strategies of the OCP genre. However, such instructions usually offer snippets of rhetorical and linguistic information. Therefore, medical students are unable to understand the implicit instructions, rhetorical strategies and medical specialists’ knowledge-in-action which further makes this daunting task of OCP more complex. This study aimed to investigate the OCPs of medical experts and students in academic context with reference to investigate the differences in performance between the experts and novices in terms of the rhetorical structure, and rhetorical and linguistic features in order to obtain insights about the genre tacit knowledge that the experts have of the professional genre (the OCP) and which the novices have not yet acquired. History taking simulations of illnesses (chest pain, Dengue fever, and numbness) were employed as research instrument. The research data comprised actual pooled presentations of 20 medical experts and 30 medical students. Additionally, semi-structured interviews were conducted with the respondents providing a supplementary support for the interpretation of the textual based findings. Discourse, genre, thematic analysis, and corpus-based approaches to text analysis were applied. Using move analysis, the present study established a framework of the rhetorical structure of the OCP genre in academic settings. The framework carries 16 distinct moves. The findings of the present study also demonstrated that medical experts shape their OCPs on the clinical course of patients by violating the traditional structure resulting in variations in the move patterns. However, medical students rigidly follow the template as they have not yet learnt the skill of synthesizing patient relevant information required for meaningful diagnosis and clinical management. In addition, the findings of the current research revealed five categories of themes in the samples such as: textual themes, interpersonal themes, subject/themes, multiple themes, and marked themes. The comparative analysis of the OCPs of medical experts and students reflected a few remarkable differences in the choices and communicative functions of the textual themes, marked themes, and subject themes. Additionally, the present research revealed that the rhetorical and linguistic knowledge of the medical experts demonstrated in the OCPs, is significantly different from the one displayed in the learners’ text. The comparative analysis of the rhetorical and linguistic features established a fact that medical students are still on the threshold of gaining access to the voice of medicine which is essential for their acculturation to the norms and values of medical discourse community. Overall, adequate gaps of genre tacit knowledge were identified in actual pooled presentations of the medical experts and novices. Finally, the current research contributed several pedagogical implications across the fields of Medical education and Applied Linguistics.